Exploring the Pedagogical Potentials and Limitations of TikTok in Language Learning - Hartono, Wira Jaya; Ramadhan, Syahrul; Tiarina, Yuli; Oktadela, Resy (Journal of Language and Literature Studies, 2026)
TikTok has quickly become one of the most widely used short-form video platforms worldwide, and its presence in language learning continues to grow. Although many digital-native learners engage with the platform daily, there is still limited research that brings together its pedagogical strengths and structural challenges in a systematic way. This study examines how TikTok can be integrated into language-learning contexts and what factors may limit its effective use. A systematic review of twenty peer-reviewed studies published between 2022 and 2024 was conducted to capture recent developments in post-pandemic digital learning. The selected studies focused on TikTok’s use in formal or semi-formal language-learning settings and were analyzed using qualitative thematic synthesis. The findings show that TikTok’s short-form and multimodal features support vocabulary development, speaking practice, pronunciation awareness, and learner engagement. Its brief and repeatable content encourages frequent exposure to language input. However, the platform’s entertainment-driven algorithm, limited capacity for deeper explanation, unequal digital access, and varying levels of teacher readiness pose challenges for structured classroom integration. Overall, TikTok offers meaningful pedagogical value when used intentionally within clear instructional frameworks. Its effectiveness depends on thoughtful alignment with learning objectives and careful integration into broader teaching strategies.